Kewenangan Pembimbing Kemasyarakatan dalam Melakukan Diversi Pra Ajudikasi (Studi pada Balai Pemasyarakatan Kelas II Ambon) - Nusaly, Angelina Imanuela Debby; Pattipawae, Dezonda Rosiana; Tuhumury, Carolina (CAPITAN: Constitutional Law & Administrative Law Review, 2023)
The criminalization of children who commit criminal offenses requires a community research report from the Correctional Center, which in this case is made by the Community Supervisor as regulated in the provisions of article 1 number 13 of Law No. 11 of 2012 concerning SPPA. One of the cases handled by the Community Supervisor is a case of persecution, based on police report Number B/113VII/1019/Reskrim. The client underwent an examination process at the Ambon Island and Lease Islands police station for allegedly committing the crime of persecution as referred to in Article 170 paragraph (1) of the Criminal Code (KUHP). The purpose of this research is to ask for consideration or advice from the Community Supervisor after the criminal offense is reported and the Community Supervisor is also not involved in the diversion process at the investigation stage. This Research uses normative legal research methods and will be studied based on positive legal provisions, as well as legal principles. and using primary, secondary and tertiary legal materials. This research uses normative legal research methods and will be studied based on positive legal provisions, as well as legal principles. and using primary, secondary and tertiary legal materials.The result and discussion shows that the authority to determine Diversion is given to law enforcement officials handling children's cases,Community Research from the Investigator as stipulated in Article 28 of Law No. 11 of 2012 concerning SPPA. After the Community Supervisor conducts the research, the results of the community research will be given to the Investigator. If the Investigators do not ask for consideration or advice from the Community Supervisor in the attempted diversion process, it can be said that the diversion process at the investigation stage is null and void.